2021
DOI: 10.1029/2020ja028994
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Zonal Wind Velocity Variation on Equatorial Plasma Bubble Occurrences Over Southeast Asia

Abstract: Localized plasma density reduction in the F region at the equator is known as the equatorial plasma bubbles (EPBs). Notably, the zonal electric fields act as the primary controller of the EPB generation (Chakrabarty et al., 2006). In the F regions, the neutral winds blowing across the magnetic field lines create an electric field (dynamo action) (Heelis et al., 1974;Rishbeth et al., 1972). An early study by Rishbeth (1971) revealed that the zonal neutral winds in the equatorial F region that blow across the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The postsunet enhancement of eastward zonal electric field and upward plasma drift due to increased zonal wind and conductivity gradient, known as PRE (Farley et al, 1986;Heelis, 2004;Eccles et al, 2015), provides a favorable condition to facilitate the growth of the R-T instability by causing the postsunset rise (PSSR) of the equatorial F-layer to higher altitudes with lower ionneutral collision frequency (e.g., Fejer et al, 1999;Sarudin et al, 2021). Along this line, some studies suggested that strong vertical plasma drift exceeding certain thresholds seems to conduct a systematic control on the development of EPBs.…”
Section: Prereversal Enhancementmentioning
confidence: 99%
“…The postsunet enhancement of eastward zonal electric field and upward plasma drift due to increased zonal wind and conductivity gradient, known as PRE (Farley et al, 1986;Heelis, 2004;Eccles et al, 2015), provides a favorable condition to facilitate the growth of the R-T instability by causing the postsunset rise (PSSR) of the equatorial F-layer to higher altitudes with lower ionneutral collision frequency (e.g., Fejer et al, 1999;Sarudin et al, 2021). Along this line, some studies suggested that strong vertical plasma drift exceeding certain thresholds seems to conduct a systematic control on the development of EPBs.…”
Section: Prereversal Enhancementmentioning
confidence: 99%
“…Figures 5 and 6 present the seasonal variation of CEJ types in the east and west, respectively. Each figure was complemented with its annual rate that was estimated according to season-Equinox (March-May, September-November), June solstice (June-August), and December solstice (December-February) [32,33] in subplots (a) and (d). Also included are a series of pie charts to represent season dominancy at different solar activity levels.…”
Section: Cej Occurrences Based On Local Times Solar Activity Levels A...mentioning
confidence: 99%
“…The changes in the occurrence characteristics of plasma irregularities from one day to the other during quiet and disturbed geomagnetic periods have been discussed in earlier literature [3,9,10]. At the equatorial regions, the zonal wind velocity variation poses a pivotal role in the generation of plasma bubbles which are the primary cause of low-latitude scintillation effects [11]. The zonal irregularities drift velocity is estimated by Vankadara et al [8] using spaced ionospheric monitoring GNSS receiver observations.…”
Section: Introductionmentioning
confidence: 99%